DETERMINANTS AND CONSEQUENCES OF WORK-LIFE BALANCE - Rosnani, Titik; Daud, Ilzar; Theresa, Revilia; Kalis, Maria Christiana Iman; Fahruna, Yulyanti (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
The work-life balance has become an important issue in the fast-paced and demanding work environment today. This study aims to analyze the determinants and consequences of work-life balance by examining the influence of working hours and job burnout on employee well-being, with the work-life balance as a mediating variable. It involved 100 active employees from the Local Government-Owned Water Utility of Pontianak City, chosen through a purposive sampling method. The data was collected using a questionnaire and analyzed using Structural Equation Modeling